2019
DOI: 10.31695/ijasre.2019.33546
|View full text |Cite
|
Sign up to set email alerts
|

Developing Empirical Models for Estimating Photo synthetically Active Radiation overAkure, South Western, Nigeria

Abstract: In this study, the measured monthly average daily global solar radiation and extraterrestrial solar radiation using the generalized 45% and 40% dataset was utilized to estimate the photosynthetically active radiation (PAR) and extraterrestrial photosynthetically active radiation (PAR 0 ) for Akure (Latitude 7.17 0 N, Longitude 5.18 0 E, and 375.0 m above sea level) Ondo State located in South Western, Nigeria. The monthly average daily sunshine hours, maximum and minimum temperature data were used to develop n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
1
0
Order By: Relevance
“…where they investigate the "photosynthetically active radiation estimations and modelling over different climatic zones in Nigeria". In another study Akpootu et al [8]. developed empirical models for Estimating Photosynthetically Active Radiation over Akure, South Western, Nigeria.…”
Section: 𝐶𝑂 2(𝑙𝑖𝑞𝑢𝑖𝑑)mentioning
confidence: 99%
“…where they investigate the "photosynthetically active radiation estimations and modelling over different climatic zones in Nigeria". In another study Akpootu et al [8]. developed empirical models for Estimating Photosynthetically Active Radiation over Akure, South Western, Nigeria.…”
Section: 𝐶𝑂 2(𝑙𝑖𝑞𝑢𝑖𝑑)mentioning
confidence: 99%
“…Up to half of the world's substantial dust emissions come from the Sahara Desert (Ogunjo et al, 2022). Generally it has been reported that in Nigeria the rainy season falls between the months of April through October and the dry season in between November through March Akpootu et al, 2019a) Kano state (Latitude: 12° 40′ and 10° 30′N, and longitude: 7° 40′ and 9° 30′ E). The climate is divided into two seasons: dry and wet.…”
Section: Study Areamentioning
confidence: 99%